Analysis of Vehicle Operating Cost Efficiency in IECO Trans Company Using Transportation Methods - Soneda, Ahmad Surya; Lestari, Yetty Dwi (Southeast Asian Business Review, 2023)
This research arose because of problems with travel costs, which the company judged were not optimal, and the profits obtained by the company were also not optimal. This research was taken from a case study at the IECO Trans company. This study aims to achieve the efficiency of the IECO Trans Company using the Transportation method. The method used from the transportation method is the northwest corner, the least cost combination, and the Vogel Approximation Method (VAM). This study uses qualitative research methods. Two data are used in this study: primary, taken from interviews and company data, and secondary, taken from previous research journals, websites, government data, and books. The results of this study will show the composition of route destinations and types of vehicles at the IECO Trans company, which results in cost efficiency. As an implementation of transportation methods and cost efficiency, the IECO Trans company will get options from the composition of route destinations and vehicle types based on analyzing transportation methods with a more efficient cost.